Real-world outcomes of anti-EGFR therapy in advanced non–small cell lung cancer EGFR mutated in Peru - Galvez-Nino, M (2023)
Background: Despite the advances in the management of advanced non–small cell lung cancer (NSCLC), the access to genetic profiling and target therapies remains a challenge in Latin America, even in countries with a higher rate of targetable mutations. The aim of this study is to evaluate the clinical outcomes of anti-epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI) treatment in a Peruvian real-world setting. Methods: This is a retrospective study of recurrent or advanced NSCLC EGFR mutated patients diagnosed and treated with anti-EGFR TKI at Instituto Nacional de Enfermedades Neoplásicas (INEN) between January 1, 2015 to December 31, 2020. The outcomes were objective response rate (ORR), progression free survival (PFS), and overall survival (OS). Results: We identify 613 stage IV or recurrent NSCLC patients who were tested for EGFR mutations and found a pathogenic mutation in 39.5% of patients. Only 51.2% of them received anti-EGFR TKI as institutional treatment. ORR was 58%, after median follow-up of 32 months, the estimated median PFS was 13.9 months (11.1–16.7 months), and the estimated median OS was 21.7 months (18.5–24.9 months). No differences were found in PFS according to line of treatment or brain metastases at diagnosis (p = 0.46 and p = 0.07, respectively), respect to OS there were no differences line of treatment (p = 0.12), significant difference were found in presence of brain metastases (p = 0.006). Conclusion: Our study demonstrates that erlotinib for advanced NSCLC harboring EGFR-activating mutations is effective even in patients usually excluded from clinical trial, like those previously exposed to one or more lines of chemotherapy or with brain metastases.